GAYA POP ART PADA KARYA DESAIN GRAFIS DI INDONESIA - Ketut Nala Hari Wardana (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2012)
Popular Art, or often abbreviated to Pop Art is an art movement whose presence is heavily influencedby popular culture phenomena that occur in society. Pop Art looks at popular culture for commercial purposesas a raw material that can be used as a source of ideas in the creation of work of art. Pop Art developed inthe years around 1960’s in America and England. Although the style of Pop Art has a long presence in the artworld, until now it seems the style of Pop Art is still one interesting source of inspiration for creative being,including graphic designers in Indonesia. This article tries to trace the presence of the Pop Art style in someform of graphic design work in Indonesia.Keywords : Pop Art, graphic design